Analysis of Living Organism in Arabic Vocabulary Meaning Perspective Biology and Lexical Meaning - Akmaliyah, Akmaliyah; Teti Ratnasih; Ayuni Adawiyah; Aldy Rialdy Atmadja; Amiq; Hendar Riyadi (Dinasti Research, 2023)
Most of Arabs people has spoken Arabic for communication. The Arabic word has a meaning to express feelings and interact socially. Lexical meaning in Arabic word has related to a specific of gender and a characteristic of living organism. The purpose of this study was to observed several meanings from the Arabic words and their relationship. In this study, semantic approach are used to analyze words lexically to find the meanings that indicate the characteristics and gender of living organism. The study found that the Arabic word has a real and a derivative meaning. As in the word father which in Arabic means Al-Abu, but it has a derivative meaning rooster. A rooster have similar character and behavior as a father in the role of the group and family member. Derivative meaning and reak meaning show that have a close relationship observed from characteristic and behavior of a living organism.